IMPLEMENTASI METODE KANGAROO MOTHER CARE UNTUK MENINGKATKAN PENGETAHUAN IBU POST PARTUM - Magdalena Limbong; Djama, Sela; Erna Kasim; Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2024)
Background :Kangaroo mother care method is direct contact with the mother which can increase the survival of the baby and get closer to the mother and baby by placing the baby on the mother's chest. Purpose: the author aims to determine the implementation of the kangaroo mother care method to increase the knowledge of post partum mothers. Method: This This study uses a descriptive case study method to describe research findings obtained systematically through studies. Conducted on 2 (two) postpartum mothers. Results: During the 3 days of meetings, the kangaroo mother care method was implemented to increase the knowledge of post partum mothers. After implementing it for three days, it can increase the knowledge of post partum mothers. Conclusion: Based on the results of the implementation of the kangaroo mother care method, it was found that the kangaroo mother care method can increase the knowledge of post partum mothers.